Perancangan Website Blogger UMKM “Rumah Parfum Lolong” Sebagai Media Pemasaran Produk - Debi Yulanda; Abhinaya Agusto Dayoh; Silva Melasari; Sularno; Rafidola Mareta Riesa (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This study aims to design the Rumah Parfum Lolong website as a medium for digital product development and marketing. In today's digital era, websites function as an important platform to increase market reach, facilitate transaction processes, and strengthen business image. This study uses a descriptive approach with literature study methods, observation, needs analysis, and direct testing of website design, customers, and potential customers. The results of the study show that the website that is designed is responsive, user-friendly, and equipped with e-commerce features that can improve operational efficiency and user convenience. Customers provide positive feedback on the visual design and ease of navigation, as well as the online ordering feature. Recommendations for further development include the addition of interactive elements, the development of product content personalization features, and strengthening digital marketing strategies through social media and email marketing. In conclusion, this website functions as an effective tool to support business development and online marketing of Rumah Parfum Lolong products.